PERANAN KEPALA SEKOLAH DALAM SUPERVISI AKADEMIK UNTUK MENINGKATKAN MUTU KINERJA GURU DI SMP NEGERI 1 BANJARMASIN - Gt. Irhamni (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
The purpose of this study was to: 1) determine how the role of the principal as a supervisor in improving teacher performance, 2) determine the mapping supervision of principals based on SWOT analysis, 3) assess educational theories relating to supervision, 4) review the tasks and role as the principal , 5) assess the performance of gurusesuai by profession, 6) examines teachers' perceptions related to supervision. The supervision of research conducted at SMPN 1 Banjarmasin. Results of the study found that: one of the efforts to improve the professional quality of teacher performance is through clinical supervision and academic supervision. Implementation of clinical supervision and academic supervision needs to be done systematically by the principal and school superintendent. This supervision aims to provide guidance to teachers in order to carry out their duties effectively and efficiently. There are a number of techniques of supervision conducted by the principal, including; engineering class visits, regular meetings with teachers and employees, and techniques related private meetings with teachers. Keyword: Supervision, Head of School, Teacher performance.